Quilombolas children's cineclub: Space for participation and dialogue - Nogueira, Valdenise Lima Pimentel (2024)
Moving away from the didactic view of cinema at school, film club activities broaden the cultural repertoire, encourage reflections on the world, problematizing thinking and making cinema. During the sessions, the right of encounter and freedom of expression mediate the participation of students, here in particular, children from the Gurugi and Ipiranga quilombos in Conde-PB, participants of the Cineclub of the Municipal School of Early Childhood Education and Elementary School José Albino Pimentel. When investigating the film project developed in this unit, we question: how was the relationship of children with this artifact configured? Anchored in this questioning, we aimed to analyze the participation of quilombola children in the school Cineclub. The methodological design was structured around qualitative studies, carried out through documentary, exploratory research. To read the data, we used the content analysis technique by Laurence Bardin (2009). The findings revealed that children participated in film club activities occupying the centrality. The film club constitutes, in this experience, a space for dialogue, pleasure and promotion of authorial audiovisual production.